Nature-inspired computing applications in advanced communication networks - Gupta, Govind P., 1979- (Advances in computer and electrical engineering (ACEE) book series., 2020)
"This book explores the application of nature-inspired intelligence for solving various optimization problems of the advanced communication networks such as WSNs, VANETs, IoT, and DSNs"--